2011
DOI: 10.1128/mcb.00981-10
|View full text |Cite
|
Sign up to set email alerts
|

BMI1 Is Recruited to DNA Breaks and Contributes to DNA Damage-Induced H2A Ubiquitination and Repair

Abstract: DNA damage activates signaling pathways that lead to modification of local chromatin and recruitment of DNA repair proteins. Multiple DNA repair proteins having ubiquitin ligase activity are recruited to sites of DNA damage, where they ubiquitinate histones and other substrates. This DNA damage-induced histone ubiquitination is thought to play a critical role in mediating the DNA damage response. We now report that the polycomb protein BMI1 is rapidly recruited to sites of DNA damage, where it persists for mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
265
4
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(288 citation statements)
references
References 61 publications
(72 reference statements)
13
265
4
4
Order By: Relevance
“…Focal accumulation of downstream factors RNF8 and 53BP1 were also reduced, as was DSB repair. At the extremes, mutation of histone H2AX lysines 119 and 120 to arginine and knockdown of RNF2 were both shown to inhibit histone H2AX phosphorylation (18,19), whereas at the other extreme, defects in signaling were not observed, but homologous recombination was impaired (15). The differences between these studies may reflect compensation by paralogues (10), differences in knockdown efficiency, and the potential reprogramming of gene expression that could accompany the lengthy incubation periods required in knockdown experiments.…”
contrasting
confidence: 43%
“…Focal accumulation of downstream factors RNF8 and 53BP1 were also reduced, as was DSB repair. At the extremes, mutation of histone H2AX lysines 119 and 120 to arginine and knockdown of RNF2 were both shown to inhibit histone H2AX phosphorylation (18,19), whereas at the other extreme, defects in signaling were not observed, but homologous recombination was impaired (15). The differences between these studies may reflect compensation by paralogues (10), differences in knockdown efficiency, and the potential reprogramming of gene expression that could accompany the lengthy incubation periods required in knockdown experiments.…”
contrasting
confidence: 43%
“…Interestingly, Bmi1 has also been reported to play a role in DNA damage repair and is also recruited to sites of laser scissors-induced local DNA breaks (19,52,53). However, Bmi1 has very different dynamics of recruitment to damage site from CBX8.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified the role of polycomb group proteins such as Bmi1 in DNA damage response (19). Polycomb genes are thought to mediate transcriptional silencing and have been implicated in the control of embryogenesis, development, stem cell self-renewal, and heritable epigenetic states, as well as cell proliferation and cancer (1, 4, 20 -27).…”
mentioning
confidence: 99%
“…3A). PcG proteins and histones are also phosphorylated upon DNA damage (22,47). Therefore, we irradiated HEK 293 cells expressing Cbx7-FLAG to induce DNA doublestranded breaks.…”
Section: Identification Of a Novel Cbx7mentioning
confidence: 99%
“…Emerging evidence suggests that PcG proteins are regulated in response to the environment or cell signaling cues through post-translational modifications, particularly phosphorylation (21)(22)(23)(24). For example, phosphorylation of Mel-18 directs Ring1b to ubiquitylate H2A in chromatin (12), and Akt-mediated EZH2 phosphorylation at serine 21 results in decreased methyltransferase activity, allowing for derepression of silenced genes (25).…”
mentioning
confidence: 99%